Metodología de trabajo desde factores motivacionales para incrementar la calidad y servuctividad en las Mipymes del sector inmobiliario de Bogotá D.C. (2021)
In the capital of Colombia, Bogotá D.C, there has been an increase in the creation and consolidation of small and medium-sized enterprises (MSMEs) in recent decades, this has conceived the generation of employment and growth opportunities for people. The small and medium-sized companies that provide real estate services are the object of study of this research since in their economic activity there is a direct interaction with the client during the servicing process and the way in which the service is offered has been determined as a matter of vital importance. so that he perceives its quality, beyond satisfying his need; and from this quality it can be distinguished that the company increases its servitude.